TDP43 Exacerbates Atherosclerosis Progression by Promoting Inflammation and Lipid Uptake of Macrophages - Huangfu, Ning; Wang, Yong; Xu, Zhenyu; Zheng, Wenyuan; Tao, Chunlan; Li, Zhenwei; Hu, Yewen; Chen, Xiaomin (Frontiers in Cell and Developmental Biology, 2021)
Objective: Atherosclerosis (AS), characterized by cholesterol overloaded-macrophages accumulation and plaque formation in blood vessels, is the major cause of cardiovascular disease. Transactive response DNA-binding protein∼43 kDa (TDP43) has recently been identified as an independent driver of neurodegenerative diseases through triggering inflammatory response. This study investigated whether TDP43 is involved in AS development, especially in macrophages-mediated-foam cell formation and inflammatory responses is still unclear. Methods: DP43 expressions in oxLDL-treated macrophages and peripheral blood mononuclear cells from patients with coronary artery disease were detected by RT-PCR, Western blot, and immunofluorescence. Gene gain or loss of functions was used to investigate the effects of TDP43 on macrophages-mediaded lipid untake and inflammation with ELISA，protein immunoprecipitation, RT-PCR, Western blot, and immunofluorescence. Macrophage TDP43 specific knockout mice with ApoE -/- background fed with western diet for 12 weeks to establish AS model, and used to explore the role of TDP43 on AS progression. Results: TDP43 expression increased in oxLDL-treated macrophages and peripheral blood mononuclear cells from patients with coronary artery disease. Furthermore, we find that TDP43 promotes activation of NF-κB to increase inflammatory factor expression in macrophages through triggering mitochondrial DNA release to activate cGAS-Sting signalling. Moreover, TDP43 strengthens lipid uptake of macrophages through regulating β-catenin and PPAR-γ complex to promote scavenger receptor gene CD36 transcription. Finally, using macrophage TDP43 specific knockout mice with ApoE -/- background fed with western diet for 12 weeks to establish AS model, we find that specific knockout of TDP43 in macrophages obviously alleviates western diet-induced AS progression in mice. Conclusions: TDP43 exacerbates atherosclerosis progression by promoting inflammation and lipid uptake of macrophages, suggesting TDP43 as a potential target for developing atherosclerotic drug.